2002
DOI: 10.4049/jimmunol.169.2.906
|View full text |Cite
|
Sign up to set email alerts
|

Antigen Presentation by CD1d Contributes to the Amplification of Th2 Responses to Schistosoma mansoni Glycoconjugates in Mice

Abstract: During murine schistosomiasis, there is a gradual switch from a predominant Th1 cytokine response to a Th2-dominated response after egg laying, an event that favors the formation of granuloma around viable eggs. Egg-derived glycoconjugates, including glycolipids, may play a crucial role in this phenomenon. In this study, we used a model of dendritic cell sensitization to study the role of egg glycoconjugates in the induction of specific immune response to soluble egg Ag (SEA) and to investigate the possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(71 citation statements)
references
References 40 publications
5
66
0
Order By: Relevance
“…MHC class I-like CD1 molecules are involved in innate immunity to many infectious agents (12)(13)(14)(15)(22)(23)(24)(25). Most often, CD1d-restricted cells belong to the invariant NKT subpopulation (12-15, 22, 24, 26), although T cells expressing noninvariant TCR have also been reported to be CD1 restricted (26 -28).…”
Section: Discussionmentioning
confidence: 99%
“…MHC class I-like CD1 molecules are involved in innate immunity to many infectious agents (12)(13)(14)(15)(22)(23)(24)(25). Most often, CD1d-restricted cells belong to the invariant NKT subpopulation (12-15, 22, 24, 26), although T cells expressing noninvariant TCR have also been reported to be CD1 restricted (26 -28).…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of SSA, SWAP and SEA was performed as described [42]. Young adult WT C57Bl/6 mice (6-8 weeks old) were purchased from Iffa Credo (l'Arbesle, France).…”
Section: Ag Preparation Mice and Infection Protocolmentioning
confidence: 99%
“…The worm burden was measured by liver perfusion 49 days after infection [42]. At the time of perfusion, the small intestines and the livers were also collected for the measurement of egg numbers within these organs.…”
Section: Analysis Of Parasitological and Pathological Parametersmentioning
confidence: 99%
“…We and others showed that glycoconjugates from egg Ags play crucial role in the Th2 response. This led us to hypothesize that egg glycolipids, through a CD1d-dependent mode of Ag presentation, could be important in this setting (Faveeuw et al, 2002;Okano et al, 1999). In agreement with this postulate, we found that CD1d-deficient ( -/-) BALB/c mice mounted a reduced Th2 response after the egg laying and developed a less marked fibrotic pathology, compared to wild type mice (Faveeuw et al, 2002).…”
Section: Trematode Infectionsmentioning
confidence: 99%
“…This led us to hypothesize that egg glycolipids, through a CD1d-dependent mode of Ag presentation, could be important in this setting (Faveeuw et al, 2002;Okano et al, 1999). In agreement with this postulate, we found that CD1d-deficient ( -/-) BALB/c mice mounted a reduced Th2 response after the egg laying and developed a less marked fibrotic pathology, compared to wild type mice (Faveeuw et al, 2002). This observation was recently confirmed in S. mansoni-infected C57Bl/6 mice (Mallevaey et al, 2007), indicating that the genetic background does not appear to influence the regulatory impact of NKT functions on the global immune response in this model.…”
Section: Trematode Infectionsmentioning
confidence: 99%